The reef ecosystem of Serrambi (Pernambuco State, Brazil): phytoplankton composition - Jales, Marina Cavalcanti; Feitosa, Fernando Antônio do Nascimento; Koening, Maria Luise; Bastos, Rafaella Brasil; Longo, Andrei Figueiredo Prates (Arquivos de Ciências do Mar, 2013)
The reef ecosystem of Serrambi is composed of fringe-type sandstone reefs that stand out because of their high biodiversity, artisanal fishing, water sports and recreational facilities. In order to evaluate the environmental conditions of this system, the structure of phytoplankton community was analyzed through samples taken in three months of the dry season and three of the rainy season, on the surface in spring tides during low tide and high tide during the day. The microphytoplankton community was represented by 159 taxa distributed among the divisions Chlorophyta and Euglenozoa with 1 taxon each ( representing 0.63 %), Cyanobacteria , with 8 taxa ( 5.03%); Dinofagellata , with 18 taxa ( 11.32%) ; Bacillariophyta , with 131 taxa identified , accounting for 82.38 %. The species that stood out as dominant were Asterionellopsis glacialis , Coscinodiscus sp ., Paralia sulcata , Thalassionema nitzschioides; and as very common , Oscillatoria princeps , Oscillatoria sp., Protoperidinium sp., Prorocentrum micans , Surirela fastuosa , Coscinodiscus sp., Grammatophora marina , Nitschia longissima , Paralia sulcata , Petroneis humerosa , Pleuro/Gyrosigma sp., Thalassiosira leptopus , Bacillaria paxillifera , Biddulphia biddulphiana and Campyloneis grevillei . According to the ecological pattern, there is a predominance of tychoplanktonics neritic (48.0 %), followed by oceanic planktonic ( 21.3%), neritic planktonic ( 16.5%), freshwater ( 5.5%) and estuarine species ( 8. 7 %). Therefore, taking into account a high specific range and good distribution of phytoplankton species, the Serrambi reef ecosystem was found to be an area free of eutrophication.